Inquiring From Within: Seventh Graders Expand the Uses of Language (2017)
ABSTRACT: This action research project was carried out with the aim of understanding how the implementation of Inquiry-Based Learning could expand the uses of language in an English as a foreign language class. The project was developed at Institución Educativa Sagrado Corazón during two school terms with a group of seventh graders. In this research study, data was gathered through a survey, an interview and a reflective journal that were first triangulated and subsequently analyzed. Findings revealed that Inquiry-Based Learning not only expanded the uses of language in the classroom, but also fostered a discussion environment with positive attitudes towards the foreign language class. Key words: Inquiry-Based Learning, uses of language, language abilities, discussion environment, use of questions